Golden Age Drama in Spain : General Consideration and Unusual Features - Leavitt, Sturgis E. (Sturgis Elleno), 1888-1976 (Studies in the Romance languages and literatures, 2019)
This volume contains sixteen articles that have been previously published in various journals and homage volumes but are now almost inaccessible, if not entirely forgotten. Two of these articles deal with the Golden Age drama in general, and the others concern rather unusual aspects of the theatrical production of the period.